Religion and State: Revisions Needed in Sri Lankan Constitutional Implications - Ratnam, Nishandey (Kathmandu School of Law Review, 2018)
The paper compares influence of religion in the Constitutional culture of Sri Lanka and India. The secular nature of both constitutions, the historic relationship between the State and religion, and religious rights is analyzed in detail. Sri Lankan Constitution has provisions of giving special recognition to the Buddhist religion while, the Indian Constitution declares itself as a secular state. However, both nations have similar societies with a lesser degree of secular political culture. An entrenched provision of the Sri Lankan Constitution stands against the good principles of constitutionalism, instrumental in transforming the constitutional culture. The benefits of the maintenance of public order and the wellbeing of all parts of the society for the nation by, allowing real freedom of religion and maintaining no partiality, secular government is yet to be recognized in the Constitutional making history of Sri Lanka and in India as well.